Image analysis of neutrophil nuclear morphology: Learning about phenotypic range and its reliable analysis from patients with pelger‐Huët‐anomaly and treated with colchicine. Issue 6 (10th February 2017) - Schnipper, Nele; Stassen, Hans H.; Kallinich, Tilmann; Sperling, Karl; Hoffmann, Katrin
Abstract : The nuclear morphology of neutrophils depends on different endogenous and exogenous factors, which can lead to hypo‐ or hypersegmentation of the normally 2–4 segmented nucleus. Hyposegmentation can be due to mutations in the LBR‐ gene (Pelger‐Huët‐Anomaly) or can be induced, for example, by colchicine treatment. The range of this phenotypic variation is known as "norm of reaction, " which can be of major relevance for clinical diagnosis and therapeutic intervention. In this project, we studied the norm of reaction in 26 subjects with 0–3 wild type LBR alleles. In addition, the phenotypic variation was analyzed in 3 patients with Familial Mediterranean Fever (FMF), before and after colchicine treatment. We measured the phenotype nuclear segmentation of neutrophils based on two conventional qualitative methods, the "rule of threads" and the "rule of thirds." In addition, we tested a morphometric quantitative approach, the "circularity index." The circularity index was superior in cases with hyposegmentation; the rule of thirds with respect to hypersegmentation. Approximately 65% of the observed phenotypic variance was explainable by the number of LBR wild type alleles. The gene‐dosage effect followed a non‐additive, hysteresis‐like characteristic with lower and upper plateaus. Colchicine treatment had a clear, although minor phenotypic effect compared to the number of LBR wild type genes or the mutation type. Thus, the nuclear morphology of granulocytes and its norm of reaction can be regarded as an excellent model both for detailing the interplay between endogenous and exogenous factors and for clinical diagnostic purposes. © 2016 International Clinical Cytometry Society